Surface water as a cause of land degradation from dryland salinity - Callow, J. Nikolaus; Hipsey, Matthew R.; Vogwill, Ryan I. J. (Hydrology and earth system sciences, 2020)
Secondary dryland salinity is a global land degradation issue. Drylands are often less developed, less well instrumented and less well understood, requiring us to adapt and impose understanding from different hydro-geomorphological settings that are better instrumented and understood. Conceptual models of secondary dryland salinity, from wet and more hydrologically connected landscapes imposed with adjustments for rainfall and streamflow, have led to the pervasive understanding that land clearing alters water balance in favour of increased infiltration and rising groundwater that bring salts to the surface. This paper presents data from an intra-catchment surface flow gauging network run for 6 years and a surface-water–groundwater (SW–GW) interaction site to assess the adequacy of our conceptual understanding of secondary dryland salinity in environments with low gradients and runoff yield. The aim is to (re-)conceptualise pathways of water and salt redistribution in dryland landscapes and to investigate the role that surface water flows and connectivity plays in land degradation from salinity in low-gradient drylands. Based on the long-term end-of-catchment gauge, average annual runoff yield is only 0.14 % of rainfall. The internal gauging network that operated from 2007–2012 found pulses of internal water (also mobilising salt) in years when no flow was recorded at the catchment outlet. Data from a surface-water–groundwater interaction site show top-down recharge of surface water early in the water year that transitions to a bottom-up system of discharge later in the water year. This connection provides a mechanism for the vertical diffusion of salts to the surface waters, followed by evapo-concentration and downstream export when depression storage thresholds are exceeded. Intervention in this landscape by constructing a broad-based channel to address these processes resulted in a 25 % increase in flow volume and a 20 % reduction in salinity by allowing the lower catchment to more effectively support bypassing of the storages in the lower landscape that would otherwise retain water and allow salt to accumulate. Results from this study suggest catchment internal redistribution of relatively fresh runoff onto the valley floor is a major contributor to the development of secondary dryland salinity. Seasonally inundated areas are subject to significant transmission losses and drive processes of vertical salt mobility. These surface flow and connectivity processes are not only acting in isolation to cause secondary salinity but are also interacting with groundwater systems responding to land clearing and processes recognised in the more conventional understanding of hillslope recharge and groundwater discharge. The study landscape appears to have three functional hydrological components: upland, hillslope “flow” landscapes that generate fresh runoff; valley floor “fill” landscapes with high transmission losses and poor flow connectivity controlled by the micro-topography that promotes a surface–groundwater connection and salt movement; and the downstream “flood” landscapes, where flows are recorded only when internal storages (fill landscapes) are exceeded. This work highlights the role of surface water processes as a contributor to land degradation by dryland salinity in low-gradient landscapes.